KHIYAR ‘AIB PERMASALAHANNYA DALAM FASAKH NIKAH: Khiyar ‘Aib dalam Fasakh Nikah: Analisis Fikih dan Implikasi Sosial terhadap Keharmonisan Keluarga - Ahmadi, Ahmadi (CV. Media Publikasi Profesional, 2025)
Marital harmony is often disrupted by various factors, including the presence of certain defects (‘Aib) or illnesses that may create disappointment and conflict between spouses. This study aims to analyze the concept of Khiyar ‘Aib as a basis for Fasakh (annulment) in Islamic jurisprudence and to examine its social implications for family stability and harmony. Employing a descriptive library research method, this study reviews classical and contemporary Islamic legal literature to identify the types of defects that grant either spouse the right to continue or terminate the marriage. The findings indicate that defects such as insanity, leprosy, vitiligo, genital impairment, and impotence can serve as valid grounds for Khiyar. Socially, the application of Khiyar ‘Aib functions as a protective mechanism to prevent harm and preserve family harmony. Thus, Khiyar ‘Aib operates not only as a legal provision in Islamic law but also as a social solution for minimizing conflict and supporting the overall well-being of families. This study contributes by highlighting the contemporary relevance of classical Fiqh principles in addressing modern family issues and by providing a theoretical foundation for strengthening family resilience.